The Role of Behavioral Attitude in Shaping Online Purchase Intention: Insights from Libyan Consumers - Amera H.M.Alzoubi; Abdalslam S. Imhmed Mohamed (African Journal of Advanced Pure and Applied Sciences, 2025)
This study examines the influence of behavioral attitude (BA) on online purchase intention (PI) among Libyan consumers within the framework of the Theory of Planned Behavior (TPB). Using survey data from 420 respondents across Tripoli, Benghazi, and Misrata, Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied. The results indicate that BA is a significant predictor of PI (β = 0.50, p < 0.001), and it mediates the effects of trust (β = 0.45), perceived usefulness (β = 0.32), and perceived risk (β = –0.21). The findings highlight the importance of trust-building, risk reduction, and emphasizing usefulness to strengthen positive attitudes toward online shopping in Libya. This study provides theoretical contributions by contextualizing TPB in a developing market and practical implications for SMEs and policymakers aiming to accelerate e-commerce adoption.